2020
DOI: 10.1016/j.redox.2020.101632
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin sensitises shikonin-induced cancer cell death mediated by oxidative stress via inhibition of the SIRT3/SOD2-AKT pathway

Abstract: Recent research suggests that melatonin (Mel), an endogenous hormone and natural supplement, possesses anti-proliferative effects and can sensitise cells to anti-cancer therapies. Although shikonin (SHK) also possesses potential anti-cancer properties, the poor solubility and severe systemic toxicity of this compound hinders its clinical usage. In this study, we combined Mel and SHK, a potentially promising chemotherapeutic drug combination, with the aim of reducing the toxicity of SHK and enhancing the overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 55 publications
0
21
1
Order By: Relevance
“…As expected, both the apoptotic rate and G0/G1 cell cycle arrest were increased in cells that received combinatorial treatment of melatonin and thapsigargin via triggering ER stress. In fact, melatonin has been shown to exhibit more promising antitumour effect when combining with a wide range of drugs, including dabrafenib, 32 shikonin, 33 valproic acid 17 and cisplatin 34 . These evidences suggested that combinatorial treatment is an effective approach to enhance the capability of melatonin to combat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, both the apoptotic rate and G0/G1 cell cycle arrest were increased in cells that received combinatorial treatment of melatonin and thapsigargin via triggering ER stress. In fact, melatonin has been shown to exhibit more promising antitumour effect when combining with a wide range of drugs, including dabrafenib, 32 shikonin, 33 valproic acid 17 and cisplatin 34 . These evidences suggested that combinatorial treatment is an effective approach to enhance the capability of melatonin to combat cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large amount of evidence on the benefits of melatonin in anticancer properties including its pro-apoptotic, anti-proliferative, anti-angiogenic, and anti-metastatic properties [ 11 , 12 , 13 ]. Melatonin also has a synergistic effect with different chemotherapeutic drugs [ 14 , 15 , 16 ]. In the clinical study, NSCLC patients concomitantly treated with melatonin exhibited better survival outcomes compared to those treated with chemotherapy alone [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, melatonin-induced oxidative stress via inhibition of the SIRT3/SOD2-AKT pathway in human histiocytic lymphoma (Li et al. 2020 ) plays a critical role in chronic Chagas disease by targeting the AMPK/NFE2L2/SIRT3 signalling pathway (Caballero et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%